Delayed visual maturation in Karen refugee infants. - Mcgready, R; Simpson, J; Arunjerdja, R; Golfetto, I; Ghebremeskel, K; Taylor, A; Siemieniuk, A; Mercuri, E; Harper, G; Dubowitz, L; Crawford, M; Nosten, F (2003)
Thirty-eight babies born to Karen mothers living in camps for displaced persons in north-western Thailand have delayed visual maturation (DVM type 1) that recovers within 6 months. Vitamin A concentrations were deficient in 16% of breast-milk samples from lactating mothers and vitamin B(1) concentrations were deficient in 60% of plasma samples. Infantile beriberi was common in this population. The levels of fatty acids in plasma and milk in Karen women were excellent at birth and in the postpartum period. The degree of deficiencies in these vitamins and the concentration of essential fatty acids in cord blood and maternal breast-milk did not correlate significantly with visual impairment in the infants. DVM might be caused by nutritional deficiency or toxic effects during critical periods of gestation that lead to delayed cortical myelination or structural defects which impinge on parietal cortex function.